Prinsip Demokrasi Dalam Mekanisme Pemilihan Kepala Daerah Oleh DPRD: Tinjauan Konstitusional Dalam Sistem Presidensial - Muh. Syahrul Ago; Firman Anugrah; Muh Rusli; Shafira Saodana; Hajriana (Universitas Musamus, 2026)
The discourse regarding the mechanism for electing regional heads through Regional People’s Representative Councils (DPRD) has re-emerged amidst various problems in the implementation of direct regional elections in Indonesia, including money politics, high political costs, and social polarization. This discourse raises constitutional debates concerning the interpretation of the phrase “elected democratically” as stipulated in Article 18 paragraph (4) of the 1945 Constitution of the Republic of Indonesia, particularly in relation to the presidential system adopted by Indonesia. This study aims to analyze the meaning of democratic principles in the mechanism for electing regional heads and to examine whether the election of regional heads by DPRD is compatible with the principles of democracy within a presidential system. This research is normative legal research employing statutory, conceptual, historical, and case approaches. The legal materials used consist of primary, secondary, and tertiary legal materials analyzed qualitatively through constitutional interpretation and legal reasoning methods. The results of the study indicate that the phrase “elected democratically” should be interpreted as the direct election of regional heads by the people as a manifestation of popular sovereignty and as a constitutional consequence of the presidential system. In a presidential system, executive legitimacy must derive directly from the people in order to maintain the principles of separation of powers, executive independence, and checks and balances. The election of regional heads by DPRD potentially weakens democratic legitimacy, creates political dependence of regional heads on DPRD, opens space for political bargaining, and shifts the character of regional governance toward a quasi-parliamentary model. Therefore, direct regional elections are not merely procedural democratic mechanisms, but also constitute a constitutional necessity in maintaining the consistency of Indonesia’s presidential system and strengthening local democracy